Paeoniflorin inhibits activation of the IRAK1-NF-κB signaling pathway in peritoneal macrophages from lupus-prone MRL/lpr mice. (November 2018) - Ji, Lina; Hou, Xiaoli; Liu, Wenhong; Deng, Xian; Jiang, Ziyan; Huang, Kaichen; Li, Rongqun
Abstract: Systemic lupus erythematosus (SLE) is a chronic and multisystemic autoimmune disease. Interleukin-1 receptor-associated kinase 1 (IRAK1) is associated with the susceptibility of SLE in humans and paeoniflorin has recently been reported to exhibit immunosuppressive properties. The aim of this study was to determine the effect of paeoniflorin on lipopolysaccharide (LPS)-triggered macrophage activation and and its role in LPS-induced IRAK1-nuclear factor κB (NF-κB) signaling pathways. Peritoneal macrophages from lupus-prone MRL/lpr mice and ICR mice were isolated, prepared and cultured. Cells were treated with LPS alone or LPS with paeoniflorin, and macrophage proliferation was analyzed using the CCK8 assay. The expression of IRAK1 in cells was analyzed by immunofluorescence staining. The level of gene expression of IRAK1, NF-κB, tumor necrosis factor-α (TNF-α), and interleukin-6 (IL-6) was measured by RT-PCR, and TNF-α, IL-6 levels in the cell supernatant were determined by ELISA. The protein expression of IRAK1 and downstream molecules tumor necrosis factor receptor-associated factor 6 (TRAF6), inhibitor of nuclear factor kappa-B kinase (IKK), NF-kappa-B inhibitor alpha (IKBα), and NF-κB was detected by Western-blot analysis. Paeoniflorin was found to decrease the phosphorylation of IRAK1 and its downstream proteins induced by LPS and inhibit the expression of TNF-α and IL-6. Taken together, the data obtained indicate that paeoniflorin inhibits LPS-induced cell activation by inhibiting the IRAK1-NF-κB pathway in MRL/lpr mouse macrophages. Therefore, paeoniflorin may be a potential therapy for SLE. Highlights: We studied the unique effects of paeoniflorin on systemic lupus erythematosus at the cellular level. Relationship between paeoniflorin and IRAK1-NF-κB signaling pathway in macrophages of lupus mice. It is helpful to find IRAK1 inhibitors to treat SLE. Extract more active ingredients from traditional Chinese medicine to treat immune diseases. Provide a reliable experimental basis for in vivo and even clinical trials.